THE EFFECT OF USING QUIZIZZ APPLICATION AS AN ENGLISH LEARNING EXERCISE IN VOCABULARY MASTERY - Apriyanti Hasibuan; Syamsiah Depalina; Nursaidah (Universitas PGRI Palembang, 2025)
This study aims to examine the impact of the Quizizz application on vocabulary mastery as part of English learning exercises among tenth-grade students at SMK Negeri 2 Panyabungan, focusing on recount text topics. It addresses challenges such as limited vocabulary mastery, low motivation and interest in learning English, and insufficient opportunities for practice. A quantitative approach with a quasi-experimental design was employed, involving experimental and control classes. Data collection included pre-tests, treatments, and post-tests using 20 multiple-choice questions on recount texts. The findings revealed that the experimental class, which used Quizizz, had a higher average post-test score (82) compared to the control class (67.5). Data analysis using the t-test showed a t-count of 4.965 and a sig. tailed (p) score of 0.001, with α = 0.05 and degrees of freedom (df) = 19. Since p < α (0.001 < 0.05), the alternative hypothesis was accepted, and the null hypothesis was rejected. These results indicate that using the Quizizz application significantly enhances students’ vocabulary mastery compared to traditional teaching methods. The study highlights the effectiveness of Quizizz in addressing vocabulary and engagement issues in English learning.